The effectiveness of corrective feedback in an oral interaction class in enhancing students' language accuracy - Abdul Kareem, Othman; Othman, Moomala (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
Public Speaking is one of the common communication-based activities worldwide. It is not a new method use by the English language teachers in this country. Public Speaking skills are essential to either adults or young learners. There are many benefits of conquering this skill such as being confident in speaking, be proactive, helping other people, boost up academic performance and many more. Unable to secure this skill is also one of the causes why the rate of unemployability in the world is on the rise. In the current phenomena, many graduates from higher learning institutions fail to master this skill even though they have graduated with distinction. This is opening chance to another set group of students who have moderate result but excellent level of speaking. They tend to excel in real life by driving their route to success whilst the group with lower language competency is still learning to master the skill in the later part. However, many language learners still neglect even after knowing the implication. Most of the activities derived from a very famous approach known as the CLT also called Communicative Language Teaching. CLT is an approach to the teaching of second and foreign languages that emphasizes interaction as both the means and the ultimate goal is learning a language. It is also referred to as “communicative approach to the teaching of foreign languages” or simply the “Communicative Approach”. CLT is a language teaching approach based on the linguistic theory of communicative competence. Using the CLT method, it is more like a normal real life situation compared to other approaches. According to Ian Tudor, the ecological perspective on language teaching focuses attention on the subjective reality which various aspects of the teaching–learning process assume for participants, and on the dynamic interaction between methodology and context. This is for the development of an approach to teaching which is locally relevant and meaningful by virtue of it being rooted in local realities. The core focus of this course is to develop students’ fluency in the target language (English). This is because the CLT approach emphasizes more on the fluency rather than accuracy. So, the researcher’s job is to carry this scrutiny to interrogate this matter to obtain the outcome of the research. The sample of this research is UPM students who are taking Oral Interaction Skills course. The students are those who got band 1 and 2 for MUET, Thus, their competency in using the language is poor. By using them as the sample, this study could compare and analyse the data before and after the study has been conducted. There are two groups involve for this study; one with public speaking activity and explicit corrective feedback by the tutor and one without feedback. The researcher will be using the 1 hour period every week to conduct the activity. On the first day of the class, the researcher will start by explaining the purpose of the study to get the best involvement from the students. Therefore, in this study, the researcher is going to investigate whether the Public Speaking activity and the explicit corrective feedback from this activity could aid the students’ language accuracy and to what extend could it improvises them.